2018
DOI: 10.1259/bjr.20170393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating which plan quality metrics are appropriate for use in lung SBRT

Abstract: Based on our study analyses, we recommend the following metrics as appropriate surrogates for establishing SBRT lung plan quality guidelines-coverage % (ICRU 62), conformity (CN or CI) and gradient (R). Furthermore, we strongly recommend that RTOG lung SBRT protocols adopt either CN or CI in place of prescription isodose to target volume ratio for conformity index evaluation. Advances in knowledge: Our study metrics are valuable tools for establishing lung SBRT plan quality guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…This concept is similar to the acceptance of dose heterogeneity within the GTV in other forms of SBRT. 8 , 14 Past SBRT trials, even with 3 and 1 fraction regimens have shown that duodenum, small bowel, and stomach constraints of V20 < 30 cc, V35 < 1 cc, and maximum dose <40 Gy are safe and well tolerated Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This concept is similar to the acceptance of dose heterogeneity within the GTV in other forms of SBRT. 8 , 14 Past SBRT trials, even with 3 and 1 fraction regimens have shown that duodenum, small bowel, and stomach constraints of V20 < 30 cc, V35 < 1 cc, and maximum dose <40 Gy are safe and well tolerated Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The RTOG protocol 9 provides guidance for acceptable values for R50% as function of the PTV volume measurement. Other RTOGdefined quantities used to assess SBRT plan quality are D2cm 7 (maximum Dose 2 cm from the PTV in any direction), V105% 9 When considering the PTV dose heterogeneity there are three metrics available: ICRU HI, 9 RTOG HI, 11 and PTV mean dose (PTV D av ). The ICRU HI, RTOG HI, and PTV D av are defined, respectively, as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Tolerances from the RTOG trial 0813, also used in the RTOG trial 0915 [15] have also been adopted internationally, however these tolerances are based on the use of 3D conformal (3D-CRT) co-planar or non-coplanar SBRT techniques, potentially calculated with Type-A algorithms, which does not reflect the techniques currently routinely used for lung SBRT [16] . The need for updating RTOG guidance has been raised in more recent publications that reviewed dose conformity in co-planar [17] , [18] , [19] , [20] , [21] or non-coplanar [22] IMRT or volumetric modulated arc therapy (VMAT) lung SBRT plans. Recommendations for plan quality metrics in other body sites are scarce; the PACE trial protocol referencing the ASTRO report [23] , that the volume ratio of the planning target volume (PTV) D 95% to the PTV should be less than 1.2.…”
Section: Introductionmentioning
confidence: 99%